Cerebrovascular Ultrasound in Stroke Prevention and Treatment. - Alexandrov, Andrei V. (John Wiley & Sons, 2007)
Intended for clinicians who are eager to learn and prepared to observe, this book is about vascular examination of patients suffering from stroke and the relevance of this information to management decisions.